1984
DOI: 10.21273/jashs.109.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Stability Differences among Fresh Market Tomato Genotypes—1. Fruit Yields

Abstract: Ten fresh market tomato (Lycopersicon esculentum Mill.) genotypes were evaluated for yield stability in 7 environments within Florida. Genotype × environment interaction was significant for yield of marketable fruit. Linear relationships between mean yields of individual genotypes and environmental mean yields were evaluated to determine genotype stability. Mean square deviations from linear regression (s2d), regression coefficients (b1) and coefficient of linear determination (R2) were used to evaluate phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…Poysa et al (15), on the other hand, reported that high-yielding tomato genotypes were unstable in yield across environments. In the present study, some of the high-yielding cultivars were fairly stable across seasons, and others were relatively unstable with respect to fruit yield, in partial agreement with the findings of others (15,17). Finlay and Wilkinson ( 9) also observed that low-yielding genotypes had above-average yield stability across environments.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Poysa et al (15), on the other hand, reported that high-yielding tomato genotypes were unstable in yield across environments. In the present study, some of the high-yielding cultivars were fairly stable across seasons, and others were relatively unstable with respect to fruit yield, in partial agreement with the findings of others (15,17). Finlay and Wilkinson ( 9) also observed that low-yielding genotypes had above-average yield stability across environments.…”
Section: Resultssupporting
confidence: 90%
“…It produced above-average yields in all years except 1980, and tended to yield more than other cultivars during the poor 1981 season, exhibiting superior adaptability compared to the other cultivars included in this study. In a study reported from Florida by Stoffella et al (17), it was observed that high-yielding fresh-market tomato genotypes had good phe- notypic stability for fruit yield. Poysa et al (15), on the other hand, reported that high-yielding tomato genotypes were unstable in yield across environments.…”
Section: Resultsmentioning
confidence: 97%
“…Plants were spaced 38 cm apart in the center of each bed and staked. Soil type, cultural practices, and fertilizer rates used in the study at Bradenton in Spring 1983 were similar to those in Spring 1982 (Stoffella et al, 1984).…”
Section: Methodsmentioning
confidence: 81%
“…Nine environments, each differing in climatic and edaphic conditions and cultural practices, were represented. Soil type and cultural practices in each environment were described by Stoffella et al (1984), except for those at Bradenton and Immokalee during Spring 1983. In the study at Immokalee (Spring 1983), beds were spaced at 1.22-m centers on an Immokalee fine sand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation